Religions and religious freedom in Portuguese prison: notes from the ethnographic fieldwork - Cerbini,Francesca (2023)
Abstract Based on the ethnographic research in a Portuguese women’s prison, this article offers a first insight into a subject scarcely discussed in Portuguese academia: the management of religion and religious freedom and diversity in prison. Through differing and intersecting views and with constant reference to the academic literature on religion in European prisons, the article highlights Catholics and Pentecostals positioning and how religion in prison designates a field in which power relations and processes of legitimation are constantly redefined and in competition. They generate dynamics of inclusion, exclusion and adaptation to the prison environment, and also innovative impulses produced by local-global fast-moving religious scenarios, settled in one of the most rigid and controversial institutions of the state.